Coking Resistance of Alumina Forming Cast Austenitic Stainless Steels - (:unkn) unknown (My University, 2017)
Coking is the process of carbon deposition from a gas phase that is encountered in many reforming, cracking and other high temperature processes. Coking in certain petrochemical processes can lead to carbon build up causing reduced process efficiency, corrosive attack and degradation of the alloy. Steam cracking of hydrocarbons is one of the most important process for manufacturing many base chemicals such as ethene, propene and other. A major influence on the energy efficiency and economics is the formation of coke on the inner wall of the reactors. With the accumulation of coke on the walls, eventually metallurgic constraints of the reactor material will force to stop the process and de-coke the reactors resulting in loss of efficiency with negative effect on the economics of the process. Materials used in these processes are fabricated from HP alloys that rely on the formation of a chromium oxide (chromia) layer as a protective layer between the bulk material and chemical byproducts. However, strong oxidation, carburization, sulfidation or nitriding can occur if the environment does not promote chromium oxide formation or if the protectivity of the scale is destroyed by other mechanisms. More recent alloys that form an alumina-based oxide layer have been recently developed for structural use in aggressive oxidizing environments. These alloys, commonly known as AFA alloys, form a protective layer of aluminum oxide (alumina) showing a promising combination of oxidation resistance, creep resistance, tensile properties, and potential for good welding behavior. An experimental high temperature coking atmosphere was constructed and used to evaluate the effects of temperature, time and metal surface roughness on the carbon deposition of two alumina forming alloys (2.6% and 3.7% Al content each). Coking conditions were simulated with multiple atmospheres including CO-H2 mixtures at moderate temperatures and ethane at higher temperatures. Carbon deposition was tracked using specific mass change of the samples as a function of exposure times and conditions. Results obtained with the alumina forming alloys were compared to a baseline HP alloy. The materials were analyzed using XRD, SEM, and optical microscopy to characterize the oxide layer formation, carbon deposition layers and carbon attack, and changes to base metal microstructure. Raman spectroscopy was used to characterize the carbon deposits. The overall resistance of the alumina-forming alloys relative to the traditional chromia forming alloys is described. Overall, AFA alloys showed better coking resistance to more aggressive environments that involve high temperature and longer times of exposure than traditional chromia-forming alloy. Therefore, this particular coking resistance make AFA alloys suitable for a wide range of energy production, chemical and process industry applications, resulting in significant cost and energy savings as well as reductions in environmental emissions.
Keywords: AFA; Austenitic Stainless Steel; Carburization; Coking; Stainless Steel